The Relationship between Workload and Work Environment on Employee Performance: A Study at PT MOD - Yonius Zebua; Krisnawati Setyaningrum Nugraheni (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study examines the relationship between workload and work environment on employee performance in Indonesia's garment manufacturing sector. Given the labor-intensive nature and competitive pressures in this industry, understanding these relationships is crucial for sustainable business practices. Using a quantitative cross-sectional design, data were collected from 104 employees at PT MOD, through validated questionnaires. Multiple regression analysis revealed that both workload (β=0.235, p=0.022) and work environment (β=0.633, p<0.001) significantly influence employee performance, explaining 70.8% of the variance (R²=0.708, F=122.352, p<0.001). Work environment demonstrated a stronger effect than workload, suggesting that investments in workplace conditions yield greater performance returns than workload optimization alone. These findings provide evidence that garment manufacturers can achieve competitive performance while maintaining employee well-being through strategic work environment improvements and balanced workload management.